Determine Eimeria Stiedae Antigens (Oocyste and Sporozoite) in Rabbits (Journal of Hama University, 2019)
The result of study showed the possibility of detection the most important immunogenic antigens from two stages of Eimeria steidea sporozoite and sporulated oocyste, which are responsible of antibody production after experimental infection.After isolation and sporulation of oocysts from liver, then applying Western Blotting technique ( to detect the most important immunogenic antigens from two stages of Eimeria steidea sporozoite and sporulated oocyste) using collected serum from  infected rabbits (day 24 post infection ) with protein extract of the sporulated oocyste and the results revealed that the immunogenic antigens of sporulated oocysts were (24.43, 26, 28.67,34.19, 57, 124.74, 130) KDa, while those recovered from the protine digestion of the  sporozoites  were (24.43, 26, 28.67) KDa.